Three new species of Syllis Savigny in Lamarck, 1818 (Annelida, Syllidae) from Chilean Patagonia - Soto, Eulogio H.; Martín, Guillermo San; Lucas, Yolanda (Zootaxa, 2020)
Three new species of the genus Syllis Savigny in Lamarck, 1818, from the Chilean Patagonia are described, figured and discussed. The specimens were collected in boulders, sediment bottoms, Macrocystis pyrifera holdfasts, and inside tubes of Chaetopterus cf. variopedatus. Syllis patagonica n. sp., is characterized by its color pattern, short, fusiform dorsal cirri, plenty of hyaline inclusions, acuminate posterior acicula, and compound chaetae with slightly bidentate falcigers. Syllis terraeignium n. sp., has similar compound chaetae, but dorsal cirri are longer than those of the above mentioned species, a long proventricle, and the posterior acicula are straight, pointed. Finally, Syllis patersoni n. sp., has a slender, elongated body, with moderately long dorsal cirri, plenty of hyaline inclusions, acuminate posterior acicula, and compound chaetae composed by falcigers and short spiniger-like.